3x=9-(-15)

Simple and best practice solution for 3x=9-(-15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x=9-(-15) equation:


Simplifying
3x = 9 + -1(-15)

Multiply -1 * -15
3x = 9 + 15

Combine like terms: 9 + 15 = 24
3x = 24

Solving
3x = 24

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '3'.
x = 8

Simplifying
x = 8

See similar equations:

| x^3-185x+800=0 | | 6x+-6=10x+2 | | -6+10-24=x | | 13-44=4(x-3)-7 | | X-99=403 | | 6x+-8=2x+2 | | 8=2w(w) | | 4xy-49x=0 | | 8x+-5=2x+10 | | 3(24-20t)+36=8(5t+1) | | Y=-5*cos*2x | | X^2-100y^2=0 | | 3x+-1=8x+7 | | 4x+-9=2x+6 | | 4x+-9=10x+3 | | 7/10c-10=2/5 | | 9a-b+4=-1 | | 3x+5x=8-2x+10 | | y=-0.004x*2+x+2.5 | | x^2+6x=432 | | -6(x+3)-12=17+1 | | 81=9xn | | f(x)=6+7lnx | | ((x-17)/(x-20))3 | | f(x)=(x-1+i)(x-1-i) | | -7-3n+2=-8n-8 | | f(x)=(x-1-i)(x-1+i) | | 7f+2f=f-6 | | 8x+-3=5x+10 | | 4a+3-a=-7+2+9 | | logf=1.406 | | -3(x+5)-41=8-37 |

Equations solver categories